Surface Structuring via Additive Manufacturing to Improve the Performance of Metal and Polymer Joints - Xin Zou; Lifu Huang; Ke Chen; Muyang Jiang; Shanyong Zhang; Min Wang; Xueming Hua; Aidang Shan (Metals, 2021)
In order to enhance the joint performance of Ti6Al4V titanium alloy (TC4) and ultra-high molecular weight polyethylene (UHMWPE) for biomedical applications, different structures were fabricated on TC4 surfaces via electron beam melting (EBM) method in this study. Macromorphologies and microinterfaces of TC4–UHMWPE joints produced via hot pressing technique were carefully characterized and analyzed. The effects of different surface structures on mechanical properties and fractured surfaces were investigated and compared. Strong direct bonding (1751 N) between UHMWPE and TC4 was achieved. The interfacial bonding behavior of TC4–UHMWPE joints was further discussed. This study demonstrates the importance of combining macro- and micromechanical interlocking, which is a promising strategy for improving metal–polymer joint performance. It also provides guidance for metal surface structuring from both theoretical and practical perspectives.